1994
DOI: 10.1152/jn.1994.72.5.2517
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of cortical blood flow and transcranial magnetic stimulation maps in human subjects after upper limb amputation

Abstract: 1. Two complimentary techniques were used to study cortical function in six human upper limb amputees: positron emission tomographic (PET) measurements of regional cerebral blood flow (rCBF) were made in subjects during limb movements to study activation of the primary motor (M1), primary somatosensory (S1), and association cortices; and electromyographic responses to transcranial magnetic stimulation (TMS) were measured in proximal upper limb muscles to assess the excitability of corticospinal neurons in subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
0
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(117 citation statements)
references
References 0 publications
10
101
0
6
Order By: Relevance
“…In contrast, Cohen et al (1991) reported that only the traumatic amputees showed enhanced reactivity in the musculature close to the amputation site, but this did not occur in a congenital amputee. The findings of Kew et al (1994) are consistent with those of the latter experiment. Kew et al studied three traumatic and three congenital amputees using positron emission tomography and transcranial magnetic stimulation during paced shoulder movements on the intact and the amputation side.…”
Section: Introductionsupporting
confidence: 90%
“…In contrast, Cohen et al (1991) reported that only the traumatic amputees showed enhanced reactivity in the musculature close to the amputation site, but this did not occur in a congenital amputee. The findings of Kew et al (1994) are consistent with those of the latter experiment. Kew et al studied three traumatic and three congenital amputees using positron emission tomography and transcranial magnetic stimulation during paced shoulder movements on the intact and the amputation side.…”
Section: Introductionsupporting
confidence: 90%
“…Similarly, subjective experiences of phantom limbs are not strongly related to sensory thresholds or tactile acuity on the stump (Hunter, Katz, & Davis, 2005). Furthermore, Kew et al (1994) found abnormal increases in the posterior parietal cortex activity related to movements of the phantom arm. Furthermore, while ablation of SI has remarkably little effect on phantom limbs (White & Sweet, 1969), some authors have reported that lesions of the posterior parietal cortex can suppress the experience of phantom limbs (Berlucchi & Aglioti, 1997).…”
Section: The Conscious Body Imagementioning
confidence: 96%
“…Learning new motor skills (Pascual-Leone et al, 1995) and performing skilled motor activities result in an expansion of the representation of the muscles involved in the task. Complete long term sensorimotor deafferentation, as in the case of limb amputation (Chen et al, 1998;Cohen et al, 1991;Kew et al, 1994;Ridding and Rothwell, 1997;Wu and Kaas, 1999) and peripheral nerve lesions (Rijntjes et al, 1997;Tinazzi et al, 1998), as well as short term deafferentation secondary to ischemic nerve block (Brasil-Neto et al, 1993;Ridding and Rothwell, 1997;Ziemann et al, 1998a;Ziemann et al, 1998b), result in an expansion of the surrounding representations.…”
Section: Introductionmentioning
confidence: 99%